2000
DOI: 10.1097/00006534-200005000-00019
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Superpulsed Carbon Dioxide Laser Energy on Keloid and Normal Dermal Fibroblast Secretion of Growth Factors: A Serum-Free Study

Abstract: An in vitro model was used to determine the effect of superpulsed CO2 laser energy on normal dermal and keloid-producing fibroblast proliferation and release of growth factors. Growth factors assayed included basic fibroblast growth factor (bFGF) and transforming growth factor beta1 (TGF-beta1). bFGF is mitogenic, inhibits collagen production, and stabilizes cellular phenotype. TGF-beta1 stimulates growth and collagen secretion and is thought to be integral to keloid formation. Growth in a serum-free medium al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
2
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 35 publications
4
52
2
2
Order By: Relevance
“…21,22 Transforming growth factor ␤1 is powerfully profibrotic, and the elevated levels of this cytokine in CO 2 lasertreated skin, peaking 2 days after treatment but remaining high for at least 28 days after resurfacing, act to support ongoing new collagen formation. The increased TGF-␤1 levels reported herein are in contrast to those noted by Nowak et al 23 in a previous study regarding levels of this cytokine after CO 2 laser treatment in an in vitro model that used keloidal and normal dermal fibroblast cell lines. 23 In that study, there was a trend toward suppression of TGF-␤ in both normal and keloidal fibroblast-derived cell lines after CO 2 laser exposure.…”
Section: Commentcontrasting
confidence: 99%
See 1 more Smart Citation
“…21,22 Transforming growth factor ␤1 is powerfully profibrotic, and the elevated levels of this cytokine in CO 2 lasertreated skin, peaking 2 days after treatment but remaining high for at least 28 days after resurfacing, act to support ongoing new collagen formation. The increased TGF-␤1 levels reported herein are in contrast to those noted by Nowak et al 23 in a previous study regarding levels of this cytokine after CO 2 laser treatment in an in vitro model that used keloidal and normal dermal fibroblast cell lines. 23 In that study, there was a trend toward suppression of TGF-␤ in both normal and keloidal fibroblast-derived cell lines after CO 2 laser exposure.…”
Section: Commentcontrasting
confidence: 99%
“…The increased TGF-␤1 levels reported herein are in contrast to those noted by Nowak et al 23 in a previous study regarding levels of this cytokine after CO 2 laser treatment in an in vitro model that used keloidal and normal dermal fibroblast cell lines. 23 In that study, there was a trend toward suppression of TGF-␤ in both normal and keloidal fibroblast-derived cell lines after CO 2 laser exposure. Whether this difference is due to the fact that the current study specifically examined photodamaged skin rather than normal and keloidal tissue or perhaps is based on inherent differences between our in vivo study design and the in vitro nature of the previous work is not clear.…”
Section: Commentcontrasting
confidence: 99%
“…It functions to stimulate mitosis, promote cell survival, inhibit collagen production, stabilize cellular phenotype, and induce angiogenesis. 25,26 It has a tissue half-life of roughly 8 hours. 27 This experiment showed a slight decrease in overall measured bFGF expression in eyelid dermal fibroblasts during the 7-day course of study when treated with 2 atm of HBO or 2 atm of HBO and NAC.…”
Section: Resultsmentioning
confidence: 99%
“…22 Interestingly, previous studies found that expression of TGFB3 mRNA levels in leiomyomas was elevated compared to matched myometrium. 23,24 These data suggest that TGFB3 may be important in uterine leiomyoma growth; however, there have been conflicting views on its effects, as high concentrations of TFGB3 did not simulate significant smooth muscle cell proliferation. 23 …”
Section: Discussionmentioning
confidence: 99%